Fraud Pentagon Analysis in Preventing Academic Fraud during Online Learning in the COVID-19 Period - Yovanka, Shania; Sugiarti, Yenny (Perspektif Akuntansi, 2024)
Students have more opportunities to commit academic fraud on online learning during the COVID-19 period. The purposes of this study are to examine the types of possible academic fraud during online learning, the motives of fraud using pentagon theory, and to provide some important recommendations for higher educationin fraud prevention. The data collection methods are questionnaires and interviews with students and lecturers at a private university in Indonesia. In addition, the data analysis is qualitative and descriptive statistical analyses. The results of this study indicate that academic fraud such as cheating, seeking help, plagiarism, and collusion occurs during online learning process. Pressure, opportunity, rationalization and arrogance are four important factors that cause academic fraud. The prevention of fraud can be through building awareness on integrity and ethical values, implementing rules and strong punishment system, building close relationship with students, improving the methods of learning and assessment, and improving internal controls.